Pelayanan Pendidikan Pada Anak Yang Mengalami Gangguan Emosi Dan Tingkah Laku - Erni Sugiarti; Silvia Oktaviani; Fauzan Said Ilham; Opi Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The aim of this research is to analyze disorders, confounding factors, approaches to dealing with them and educational service models for children with emotional and behavioral disorders. This research was motivated by various cases related to the low level of education of children with special needs, many of whom even experienced discriminatory treatment. The research method used is descriptive with data collection techniques in the form of a literature review of references relating to the various symptoms observed. The collected data was analyzed descriptively and qualitatively so that differences in the characteristics and models of educational services provided to children with special needs and emotional and behavioral disorders were visible. The research results show that children with emotional and behavioral disorders show characteristics such as intelligence and learning ability, social and emotional traits, as well as immature and withdrawn behavior. Models of educational services for children who experience emotional and behavioral disorders can be grouped into three, namely. differentiated education services, integrated/integrated education services, and inclusive education using individual and group approaches.